Affine Hecke algebras and quantum symmetric pairs - Fan, Zhaobing; Lai, Chun-Ju; Li, Yiqiang; Luo, Li; Wang, Weiqiang (Memoirs of the American Mathematical Society, 2023)
We introduce an affine Schur algebra via the affine Hecke algebra associated to Weyl group of affine type C. We establish multiplication formulas on the affine Hecke algebra and affine Schur algebra. Then we construct monomial bases and canonical bases for the affine Schur algebra. The multiplication formula allows us to establish a stabilization property of the family of affine Schur algebras that leads to the modified version of an algebra